Analisis Komparatif Pemilihan Akad Murabahah il Wakalah Dan Akad Salam Bil Wakalah Dalam Pembiayaan Perbankan Syariah Perspektif Hukum Islam - Suhaeri Heri (Muhammadiyah University of Surabaya, 2025)
This study discusses the reasons for the dominant use of murabahah bil wakalah contracts in Islamic banking financing compared to salam bil wakalah contracts from the perspective of Islamic law. Although the salam bil wakalah contract has been recognized as valid by the DSN-MUI fatwa and has great potential in supporting financing for the productive sector, Islamic banking practices in Indonesia prefer the murabahah bil wakalah contract which is considered more efficient and has minimal risk. The problem of this research is why the murabahah bil wakalah contract is preferred and what are the obstacles to using the salam bil wakalah contract according to Islamic law. The research method used is library research with a descriptive qualitative approach through analysis of literature, fatwas, and related documents. Research results The use of the murabahah bil wakalah contract is more in line with the reality of Islamic banking financing in Indonesia, where customers generally do not have the initial funds to purchase the goods they need.